Tamarix honey phenolics attenuate cisplatin-induced kidney toxicity by inhibition of inflammation mediated IL-6/STAT3/TNF-α and oxidative stress-dependent Nrf2/caspase-3 apoptotic signaling pathways - Aati, Hanan; Aati, Sultan Y.; Bahr, Hebatallah S.; Abdel-Sattar, Asmaa Ramadan; Embaby, Marwa Ahmed; Reda, Ahmed M.; Abdelmohsen, Usama Ramadan; Bringmann, Gerhard; Hassan, Hossam M.; Darwish, Mostafa A. (Frontiers in Pharmacology, 2025)
IntroductionCisplatin (CIS) is a productive chemotherapeutic agent that is effective against a variety of cancer types. Its utilization is linked to acute kidney injury and other adverse consequences. Among its toxic effects are oxidative stress, apoptosis as well as inflammation. Saudi Tamarix honey (STH) is a valuable product with plentiful nutritional and health benefits, demonstrating advantageous effects against inflammation and oxidative stress. Therefore, this study examined the potential of STH to prevent oxidative stress, apoptosis, inflammation, and kidney impairment that are induced by CIS in rats, pointing to the entanglement of the Nrf2, the caspase-3, and the IL-6/STAT3/TNF-α signaling pathways.MethodHistopathological examinations of the kidney were also used to evaluate cisplatin-induced nephrotoxicity. The rats received STH (50, 100 mg/kg) for 10 days and were challenged with a single dose of CIS (7 mg/kg) on day 7.ResultsCIS caused injury to the glomeruli and the tubules, increased lipid peroxidation, TNF-α, IL-6, cleaved caspase-3, and decreased cellular antioxidants in the kidneys of rats. STH effectively prevented tissue injury, and ameliorated oxidative stress, inflammatory markers, in addition to caspase-3 in CIS-administered rats. STH is rich with antioxidants, suppressed STAT3 protein expression, and upregulated Nrf2 in CIS-administered rats. In conclusion, STH mitigated CIS-induced kidney injury by reducing oxidative stress, suppressing STAT3 and caspase-3, inhibiting pro-inflammatory mediators, and enhancing Nrf2 signaling. On the other hand, metabolomic profiling proposed the presence of 15 metabolites belonging to the chemical classes, phenolic acids, flavonoids and sterols, where phenolic acids were the most abundant classes.